Shelf-life prediction of smoked catfish coated with chitosan and red galangal extract - Dewi Fortuna Ayu; Raswen Efendi; Yanti Nopiani; Edo Saputra; Ahmad Ibrahim Hasibuan; Rahmadini Payla Juarsa; Husnul Husnul (Brazilian Journal of Food Technology)
Abstract This research aimed to estimate the shelf-life of smoked shark catfish coated with chitosan and red galangal extract and packed with aluminum foil using the acceleration method. The prediction of the smoked catfish shelf-life was carried out by storing the smoked catfish at temperatures of 35, 45, and 55 °C for 30 days. The parameters observed during storage were color, sensory score of rancidity, and thiobarbituric acid (TBA) value. Data were analyzed using linear regression, and the equations obtained were used to calculate the shelf-life of smoked catfish at 30 °C. The color values of L*, a*, and b* of the smoked catfish coated with chitosan decreased faster, and the shelf-life was shorter than that of the smoked catfish coated with chitosan and red galangal extract. The shelf-life and activation energy of smoked catfish coated with chitosan at 30 °C were 29.63 days and 2873.146 cal/mol, while the smoked catfish coated with chitosan and red galangal extract were 38.52 days and 3380.371 cal/mol, respectively.